Toxicity assessment and bioimaging potential of carbon dots synthesized from banana peel in zebrafish model - Wijayanti, Ni PAD.; Permatasari, Fitri A.; Damayanti, Sophi; Anggadiredja, Kusnandar; Iskandar, Fery; Wibowo, Indra; Rachmawati, Heni (Narra J, 2024)
Zebrafish serve as a pivotal model for bioimaging and toxicity assessments; however, the toxicity of banana peel-derived carbon dots in zebrafish has not been previously reported. The aim of this study was to assess the toxicity of carbon dots derived from banana peel in zebrafish, focusing on two types prepared through hydrothermal and pyrolysis methods. Banana peels were synthesized using hydrothermal and pyrolysis techniques and then compared for characteristics, bioimaging ability, and toxicity in zebrafish as an animal model. Pyrolysis-derived banana peel and hydrothermal-derived banana peel showed blue emission under ultraviolet light, indicating excitation-dependent behavior. To test their potential application for bioimaging, a soaking method was used using zebrafish that showed fluorescence intensity in the eyes, abdomen, and tail of zebrafish. Toxicity comparison showed that pyrolysis-derived banana peel had lower toxicity with 50% lethal concentrations (LC50) of 1707.3 ppm than hydrothermal-derived banana peel (LC50 993 ppm) in zebrafish. Both types of carbon dots showed significant differences (p<0.05) in hatching rates at 96 and 120 hours of exposure. Of the two methods for carbon dot synthesis from banana peel, the pyrolysis method had a higher toxicity threshold than the hydrothermal method, as indicated by the LC50 value and the number of zebrafish embryos that died, hatched delayed, and experienced malformation during their development.